2021
DOI: 10.5114/aoms.2019.84470
|View full text |Cite
|
Sign up to set email alerts
|

NGS study of glucocorticoids response genes in inflammatory bowel disease patients

Abstract: Introduction: Despite intensive research and a long history of glucocorticoids being applied in various clinical areas, they still generate a challenge for personalized medicine by causing resistance or dependence in nearly 50% of patients treated. The objective of the present study was to determine the genetic predictors of variable reactions in inflammatory bowel disease patients to glucocorticoid therapy. Therefore, based on the current knowledge on how glucocorticoids act, we have compiled a panel of 21 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Another study showed that the combination of glucocorticoid receptor (GR) and FKBP5 (the cg25114611 annotated to the FKBP5 gene) mutational analyses could help to identify subgroups of CD with higher chances of benefitting from glucocorticoid treatment ( Maltese et al, 2012 ). FKBP5 revealed a significant impact on the glucocorticoid treatment response, which could result in valuable pharmacogenetic biomarkers after being confirmed in other populations and in functional studies ( Skrzypczak-Zielinska et al, 2021 ). In addition, Tobi et al (2018) illustrated that DNA methylation acted as a mediator of the association between prenatal adversity and risk factors for metabolic disease, and it has been shown that methylation of cg09349128 was associated with the expression of PIM3, a gene implicated in cell growth and energy metabolism ( Beharry et al, 2011 ) and glucose-stimulated insulin secretion in β cells ( Vlacich et al, 2010 ).…”
Section: Discussionmentioning
confidence: 94%
“…Another study showed that the combination of glucocorticoid receptor (GR) and FKBP5 (the cg25114611 annotated to the FKBP5 gene) mutational analyses could help to identify subgroups of CD with higher chances of benefitting from glucocorticoid treatment ( Maltese et al, 2012 ). FKBP5 revealed a significant impact on the glucocorticoid treatment response, which could result in valuable pharmacogenetic biomarkers after being confirmed in other populations and in functional studies ( Skrzypczak-Zielinska et al, 2021 ). In addition, Tobi et al (2018) illustrated that DNA methylation acted as a mediator of the association between prenatal adversity and risk factors for metabolic disease, and it has been shown that methylation of cg09349128 was associated with the expression of PIM3, a gene implicated in cell growth and energy metabolism ( Beharry et al, 2011 ) and glucose-stimulated insulin secretion in β cells ( Vlacich et al, 2010 ).…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, construction of the drug–compound–target–disease and PPI networks showed that the HSP90AA1 gene was the key intersecting gene between both. This gene was found to be associated with the glucocorticoid response and severity of fatigue in patients with CD ( Grimstad et al, 2020 ; Skrzypczak-Zielinska et al, 2021 ). Molecular docking showed that the protein encoded by the HSP90AA1 gene bound to aureusidin, the bioactive compound of P. chinensis , which had various anti-inflammatory effects on inflammation-related diseases ( Ren et al, 2020 ; Yang et al, 2020 ; Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK14, an isoform of serine/threonine-specific kinase (SAPKs) is a major subfamily of mitogen-activated protein kinase, which plays an important role in TNF-alpha production ( 66 ). Patients with mutated MAPK14 showed adverse therapeutic effects when treated with glucocorticoid, suggesting that MAPK14 is a potential biomarker to predict therapeutic responses ( 67 ). Research has found that UC patients with high MAPK14 expression experience more severe abdominal pain than patients with low MAPK14 expression ( 68 ).…”
Section: Discussionmentioning
confidence: 99%